THE PERCEPTION OF TOURIST ELDERLY VISIT TO ANCOL - Ratnasari, Kania; Bhudiharty, Susy (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
This study aims to find out the profile of elderly tourists who come to visit Ancol Beach, find out how important attributes / facilities Ancol Coast needed by elderly tourists, knowing the performance of the attributes / facilities provided by the Ancol and know how the perception of elderly tourists in a visit to the Beach Ancol. The method used for this research is the method of Importance Performance Analysis (IPA) by using Cartesian diagram. Data collection techniques obtained through interviews and questionnaires distributed for elderly visitors as many as 40 people. Data processing using the calculation of the average importance and performance, the calculation of the level of conformity followed by the making of Cartesian diagram.Results of the calculation of the level of interests and performance of visitors Ancol Coast by using the level of conformity that indicates a mismatch between expectations with the reality of respondents. Thus, the existing attributes have not been able to give satisfaction to the visitors of Ancol Beach. From the side of Cartesian diagram, there are 11 attributes that enter into Quadrant I and there are 2 attributes that enter into Quadrant II, whereas there is not one attribute that enter into Quadrant III and IV. The ideal attributes are in quadrant II for attributes of fresh coastal air climate and cafÃ© / resto availability.